Pengaruh Pengumuman Peringkat Obligasi Terhadap Reaksi Pasar Saham di Bursa Efek Indonesia - annisa maulida harahap; syahyunan MSi (Universitas Sumatera Utara, 2013)
Abstract Research question in this study was whether the bond rating upgrade announcements positively affect on the stock market reaction to Bursa Efek Indonesia and whether the bond rating downgrade announcements negatively affect the stock market reaction to Bursa Efek Indonesia. Purpose of this study was to investigate and analyze the positive effect of the bond rating upgrade announcements on the stock market reaction to Bursa Efek Indonesia and to investigate and analyze the negative effect of the bond rating downgrade announcements on the stock market reaction to Bursa Efek Indonesia. The hypotheses in this study were: 1) The bond rating upgrade announcements positively effect on the stock market reaction to Bursa Efek Indonesia and, 2) The bond rating downgrade announcements negatively effect on the stock market reaction to Bursa Efek Indonesia. Sampling method in this study used a non-probability sampling design with purposive sampling method. Population of research was issuers that experienced bond rating change announcements by PT PEFINDO during the period 2006 to 2012. Research sample consisted of 24 issuers that had 37 bond rating upgrade announcements and 8 bond rating downgrade announcements. The method of analysis used one-sample t test for the first hypothesis and the second hypothesis. The Results of research were: 1) The bond rating upgrade announcements positively and not significantly effect on the stock market reaction to the Bursa Efek Indonesia and, 2) The bond rating downgrade announcements negatively and not significantly effect on the stock market reaction to the Bursa Efek Indonesia. Key Word: Bond Rating, Stock Market Reaction.